Mobile Application Development For Digitalization In The Service Sector “ReHome” - Alfarizi, Muhammad Fadhillah; Nasir, Muhammad (Politeknik Negeri Lhokseumawe, 2025)
This research presents the development of ReHome, an Android-based mobile application designed to support the digitalization of architectural design services. The application provides various features that enable users to access house designs, save references, and communicate directly with architects. ReHome was developed using the Rapid Application Development (RAD) methodology to ensure rapid and adaptive system development according to user needs. The application interface was designed using Figma and implemented in Android Studio environment with Java/Kotlin programming languages, integrated with Firebase for authentication and data storage. The application features include user login and registration, main dashboard with design categories and search functionality, detailed house design views, user-architect communication system, architect portfolio management, and admin dashboard for design verification. Testing was conducted using black box testing methods for functional validation. The results show that ReHome successfully achieves its main objective of supporting the digitalization of the architectural design service industry by providing an efficient, modern, and interactive platform. The application enables users to access house design services efficiently while allowing service providers to reach more clients through digital platforms. ReHome demonstrates the practical application of digitalization concepts in the Industry 4.0 era and has great potential for further development with additional features such as integrated service booking systems and more complex admin dashboards.